Analysis of the Effectiveness of Fundraising Strategies as an Improvement of Zakat Management at Baitul Maal Hidayatullah Ponorogo (2020-2022) - Ernaldo Fikrul Arifin; Zulfatus Sa'diah (JURNAL PENDIDIKAN IPS, 2025)
This study aims to analyze the effectiveness of the fundraising strategy implemented by Baitul Maal Hidayatullah (BMH) Ponorogo in the period 2020–2022 in order to improve zakat management. In the context of Islam, zakat is a main pillar that plays an important role in economic development and poverty alleviation. BMH Ponorogo as a zakat management institution implements various strategies, both offline and online, to optimize zakat fund collection. This study uses a qualitative approach with a case study method, supported by quantitative data from financial reports, in-depth interviews, and surveys of donors and beneficiaries. The results of the study show that the digital fundraising strategy through social media, collaboration with companies, and the implementation of social programs have significantly increased the number of muzaki and zakat receipts, especially in 2022 after experiencing a decline in the previous year. Despite challenges such as low public understanding and high competition between zakat institutions, the effectiveness of BMH's fundraising strategy is considered quite high, marked by the achievement of revenue targets that always exceed expectations. This study emphasizes the importance of innovation, transparency, and integrity in zakat management to maintain public trust and participation.